2014
DOI: 10.1287/mnsc.2013.1834
|View full text |Cite
|
Sign up to set email alerts
|

When Kerry Met Sally: Politics and Perceptions in the Demand for Movies

Abstract: M ovie producers and exhibitors make various decisions requiring an understanding of moviegoer's preferences at the local level. Two examples of such decisions are exhibitors' allocation of screens to movies and producers' allocation of advertising across different regions of the country. This study presents a predictive model of local demand for movies with two unique features. First, arguing that consumers' political tendencies have an unutilized predictive power for marketing models, we allow consumers' het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 47 publications
1
18
0
2
Order By: Relevance
“…Finally, our findings contribute to emerging evidence on the role of political ideology in marketing (Fernandes and Mandel 2014;Khan et al 2013;Kidwell et al 2013;Roos and Shachar 2014;Winterich et al 2012) by extending the influence of ideology to consumers' attempts to differentiate their identity. Our work thereby suggests that identity is a useful framework for studying the role of ideology in consumer behavior.…”
Section: Theoretical Implicationssupporting
confidence: 54%
See 2 more Smart Citations
“…Finally, our findings contribute to emerging evidence on the role of political ideology in marketing (Fernandes and Mandel 2014;Khan et al 2013;Kidwell et al 2013;Roos and Shachar 2014;Winterich et al 2012) by extending the influence of ideology to consumers' attempts to differentiate their identity. Our work thereby suggests that identity is a useful framework for studying the role of ideology in consumer behavior.…”
Section: Theoretical Implicationssupporting
confidence: 54%
“…This yielded 24 search indexes in each of Political Ideology. We collected two measures that have previously been used as proxies of state political ideology (Jost et al 2003;Khan et al 2013;Roos and Shachar 2014): (1) the percentage of people who self-identified as conservative in each state in the 2009-2015 Gallup state of the states metrics (M ¼ 38.77, SD ¼ 5.59), and (2) the number of times that the state was carried by a Republican candidate in the five presidential elections from 2000 to 2016 (M ¼ 2.74, SD ¼ 2.24). The two measures were strongly correlated (r ¼ .89, p < .01).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 We measure a movie's targeted audience size using information about the exhibition intensity of a movie in its first week in a given country. The number of opening screens is an important strategic variable and is closely related to the targeted audience and expected demand for a movie (Roos and Shachar, 2014). We do not directly use absolute numbers or market shares per country and week because such measures are endogenous (Sawhney and Eliashberg, 1996: 119).…”
Section: Baseline Resultsmentioning
confidence: 99%
“…We use a "structural MDS" approach (Goettler and Shachar, 2001;Roos and Shachar, 2011) in formulating the match parameters (the δ ij 's in 2.6). This approach has several advantages, including parsimony and ease of interpretation, as it can produce a joint map of consumer preferences and blog locations.…”
Section: Consumer-specific Match Utilitymentioning
confidence: 99%